1987
DOI: 10.1002/art.1780300202
|View full text |Cite
|
Sign up to set email alerts
|

Mast cell numbers in rheumatoid synovial tissues

Abstract: Synovial biopsy specimens from 20 patients with rheumatoid arthritis were subjected to quantitative analysis for several parameters of inflammation and for enumeration of synovial tissue mast cells. Strong positive correlations were found between numbers of mast cells per cubic millimeter of synovial tissue and the following synovial tissue parameters: inflammatory index (a quantification of lymphocytic infiltration), Leu‐3a grade (T helper/inducer lymphocytes), Leu‐1 grade (T lymphocyte), and plasma cell grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…The synovium proliferates and grows in a manner similar to cancer tissue. MCs residing in synovial tissue are often in the activated, degranulated state (23, 25, 26). In allergic reactions, MCs are usually activated through their high‐affinity IgE receptors (FcɛRI).…”
Section: Mcs In Ramentioning
confidence: 99%
See 1 more Smart Citation
“…The synovium proliferates and grows in a manner similar to cancer tissue. MCs residing in synovial tissue are often in the activated, degranulated state (23, 25, 26). In allergic reactions, MCs are usually activated through their high‐affinity IgE receptors (FcɛRI).…”
Section: Mcs In Ramentioning
confidence: 99%
“…MCs often appear to be in an activated state in synovial tissue (23, 25, 26). In addition, increased levels of MC‐derived mediators, histamine and tryptase, have been detected in synovial fluids of RA patients, which also suggests that MCs in RA synovium are continuously activated (36, 37).…”
Section: Mcs In Ramentioning
confidence: 99%
“…Moreover, MCs are implicated to have a role in inflammatory diseases such as autoimmune arthritis 17 18 . Interestingly, both human patients with rheumatoid arthritis (RA) and mice subjected to the collagen-induced arthritis (CIA) RA model show increased numbers of MCs in the inflamed synovium 17 19 20 21 22 23 24 , suggesting that MCs contribute to this type of pathology. Indeed, there are several studies based on the use of MC-deficient animals that support a pathogenic role of MCs in various models of arthritis, both passively 25 and actively 18 induced.…”
mentioning
confidence: 99%
“…However, several observations that would be in favor of our concept exist: Malone et al [34] have reported on an inverse correlation between the number of MC and the amount of fibrin deposits in synovial tissue in patients with rheumatoid arthritis. In addition, the MC-dependent (rapid) fibrin deposition in experimental animals seems to resolve more rapidly as compared to an MC-independent fibrin deposition.…”
Section: Clinical Significancementioning
confidence: 88%